Relaxing the <svg xmlns:xlink="http://www.w3.org/1999/xlink" xmlns="http://www.w3.org/2000/svg" style="vertical-align:-0.2723999pt" id="M1" height="15.3681pt" version="1.1" viewBox="-0.0657574 -15.0957 21.9182 15.3681" width="21.9182pt"><g transform="matrix(.017,0,0,-0.017,0,0)"><path id="g113-88" d="M962 650H739L732 622L760 619C812 613 819 604 798 552C760 457 671 267 606 131H604L511 638H480L237 131H233L183 554C177 607 183 614 226 619L248 622L257 650H24L17 622C88 615 92 611 103 524L173 -11H203L450 491H453L543 -11H575L839 529C882 609 886 613 953 622L962 650Z"/></g><g transform="matrix(.012,0,0,-0.012,16.723,-7.578)"><path id="g50-31" d="M310 541L304 571C290 586 211 619 185 610L80 76L131 52L310 541Z"/></g> Constraint on Compact Extradimension - Arun, Mathew Thomas (Advances in High Energy Physics, 2022)
In this paper, we study the constraint on brane tension and compactification scale for models with brane fluctuations using the results from the direct search of W′ at 13 TeV LHC, with an integrated luminosity of 36.1fb−1, in the case for which branon forms the entire cold dark matter. The inclusion of these brane fluctuations suppresses the KK-mode couplings to brane localised matter fields. Unlike the rigid brane scenario, where the compactification scale gets constrained to 1/R>5.2 TeV, here we show that compactification scales as small as ~1 TeV are allowed for brane tensions of similar strength.